Austerity measures and municipalities: the case of Denmark. (August 2014) - Mailand, Mikkel
Danish municipalities have gone through a number of austerity-related government initiatives with consequences for job levels and public services. Moreover, the 'regulation mechanism', which ties public sector wages to wage development in the private sector, has worked as an indirect austerity measure leading to a quasi-pay freeze during the public sector collective bargaining rounds in 2011 and 2013. It is difficult, however, to isolate crisis-related consequences from other factors such as demographic development, outsourcing and pre-crisis reform. Social dialogue has played a very limited role in relation to the direct austerity measures, though case studies show that social dialogue at the local level has played a role in the implementation of austerity and restructuring measures. In the education area, working time was removed from the local bargaining agenda after a lock-out and government intervention in the 2013 bargaining round, but beyond this area no major changes in social dialogue institutions have taken place.